Migration interstate cearense: trends an inflections during the period 1950 to 2010 - de Queiroz, Silvana Nunes; Baeninger, Rosana (Geografares, 2017)
The aim of this study is to analyze the landscape of Ceará interstate migration, from the year 1950. The interpretation of the conditions of the migration process is done from the historical-structural approach, where migration is element of regional inequality by the expansion of capitalism. In order to measure evolution and changes in migratory trends from and to Ceará, we work with the "lifetime migrant". The Statistical Yearbook of Brazil and the microdata of the Demographic Census (IBGE) are the main sources of information. The main results show that, only from the 2000s, Ceará has reduced its population losses. Keywords: Migration; Ceará; Regional Inequality.